88 Improving Clinical Effectiveness At Identifying Patients Requiring Advanced Care Plans. (16th March 2021) - Nemchand, P; Hassan, D; Steel, A
Abstract: Our project was conducted in a district general hospital across five acute geriatric wards. Our team included consultants, registrars, and ward matrons. The project focused on improvement of care for geriatric inpatients, with moderate to severe frailty. Advanced care planning (ACP) columns are displayed on white boards. They indicate whether ACPs are required/initiated for each patient. When previously utilised, ACPs were initiated for 78% of appropriate patients [1]. Following a change in staff and reduction in awareness/education, the ACP column use reduced with fewer ACPs established. Our goals were to ensure completion of the ACP column, encourage junior doctor/nurse involvement and trigger a greater number of appropriate ACPs initiated Improvement in ACP practice was addressed by daily board round review of appropriate patients for ACP, increasing awareness of ACP triggers and education around discussion content. Interventions consisted of: 1, a flow-chart adjacent to white boards prompting "Do not attempt resuscitation (DNAR)" and ACP processes. This signposted staff to information on ACP triggers and "how to start a conversation". 2 Involving registrar "champions" on each ward. We explained our intervention to all team members to encourage engagement. Data from the ACP columns were audited prior to intervention, 2 weeks and 6 weeks after intervention. There was a 54% increase in ACP documentation after 6 weeks across the wards. The improvement in the use of the ACP column correlated with a greater number of ACPs initiated. This facilitated an increase in consideration of patient wishes towards the end of life. Increasing use of a daily ACP prompts on board rounds triggers an increase in ACP implementation for appropriate patients. Sustainability was achieved by recruitment of ward "ACP champions". Junior doctors/matrons were more empowered to discuss ACPs. Results were presented at departmental teaching to reinforce the positive impact of the intervention.